2020
DOI: 10.1177/1750458920928473
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of acute appendicitis and associated factors among admitted patients with a diagnosis of acute abdomen in Debre Markos Referral Hospital, Amhara Region, North West Ethiopia

Abstract: Introduction Appendicitis is an inflammation of the vermiform appendix and is one of the most common causes of an acute abdomen in young adults. If left untreated, it can lead to appendiceal abscess, perforation and peritonitis. Objective To assess treatment outcomes of acute appendicitis and associated factors among admitted patients with a diagnosis of acute abdomen. Methods and materials: A cross sectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
0
7
1
Order By: Relevance
“…Lastly, the investigators confirmed that age was not an independent predictor of post-operation unfavorable outcomes of appendectomy. This result has disagreements with the previous studies 15 , 17 , 42 in which elderly patients are more at risk to develop post-operation negative outcomes. This disagreement may be due to the study period and socio-demographic variations of the studies.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Lastly, the investigators confirmed that age was not an independent predictor of post-operation unfavorable outcomes of appendectomy. This result has disagreements with the previous studies 15 , 17 , 42 in which elderly patients are more at risk to develop post-operation negative outcomes. This disagreement may be due to the study period and socio-demographic variations of the studies.…”
Section: Discussioncontrasting
confidence: 74%
“…8–11 In the last few decades, in African countries, appendicitis frequency is increasingly noted. 12–14 In Ethiopia, the incidence is increasing through time such as in Debre Markos Referral Hospital (26.6%), 15 as stated by Mohammed S et al a studies in 2014 by Nebyou S et al (28%), in 2019 by Wosen MT (55.4%), 16 and 36 deaths in Gondar University Hospital. 17…”
Section: Introductionmentioning
confidence: 90%
“…All the studies were quantitative. The most common study designs were cross‐sectional 38 (48.7%) [14–52] and cohort 32 (41.0%) [26, 52–83] (Table 1). Study periods ranged from two months to twenty‐five years.…”
Section: Resultsmentioning
confidence: 99%
“…Study periods ranged from two months to twenty‐five years. There were 27 097 patients across the seventy‐eight studies with a median of 166 (IQR: 10–3717) [14–28, 30, 32–42, 44–61, 63, 64, 66–82, 84–92].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation